2009
DOI: 10.1002/lary.20124
|View full text |Cite
|
Sign up to set email alerts
|

Transoral resection of tonsillar squamous cell carcinoma

Abstract: Transoral resection of tonsillar SCCA with or without postoperative adjuvant therapy provided excellent locoregional control and minimized treatment-related morbidity. We believe that transoral resection is the optimal treatment for patients with oropharyngeal SCCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
95
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 23 publications
6
95
0
3
Order By: Relevance
“…Previous studies have confirmed that transoral surgical management of oropharyngeal cancer, especially early stage, is a safe treatment option with good functional re- sults. [10][11][12][13][14] In the present study, we demonstrate 2-year survival data for primary treatment of oropharyngeal disease of 89.3%, which is comparable to standard treatment modalities.…”
Section: Commentsupporting
confidence: 62%
“…Previous studies have confirmed that transoral surgical management of oropharyngeal cancer, especially early stage, is a safe treatment option with good functional re- sults. [10][11][12][13][14] In the present study, we demonstrate 2-year survival data for primary treatment of oropharyngeal disease of 89.3%, which is comparable to standard treatment modalities.…”
Section: Commentsupporting
confidence: 62%
“…[9][10][11] Transoral robotik cerrahinin onkolojik sonuçlarının iyi olduğu ve morbiditeyi sınırladığı literatürde çeşitli çalışmalarla ortaya konmuştur. [17] Moore ve ark. [17] TORC orofarenks YHK uzun dönem sonuçlarını yayınladıkları çalışmada, TORC'un onkolojik sonuçlarının diğer cerrahi ve cerrahi dışı tedavilere kıyasla eşit veya daha iyi olduğunu belirtmiştir.…”
Section: Discussionunclassified
“…[17] Moore ve ark. [17] TORC orofarenks YHK uzun dönem sonuçlarını yayınladıkları çalışmada, TORC'un onkolojik sonuçlarının diğer cerrahi ve cerrahi dışı tedavilere kıyasla eşit veya daha iyi olduğunu belirtmiştir. Ancak TORC'un henüz sadece belli merkezlerde kullanılması, maliyet etkinliği açısından pahalı bir teknik olması yaygın kullanımını kısıtlamaktadır.…”
Section: Discussionunclassified
“…While the 5-year survival for surgically treated tonsillar cancer is about 30% [27] , recent studies have demonstrated more promising results. Moore et al [28] report a 94% disease-specific survival in stage III and IV tonsillar carcinomas treated with transoral resection and adjuvant therapy. Rich et al [29] reported 2-year and 5-year disease-specific survivals of 96 and 92% for stage III and IV oropharyngeal carcinoma treated with transoral laser microsurgery.…”
Section: Discussionmentioning
confidence: 99%